Attitudinal versus psychosocial resource measures of career adaptability and boundaryless career attitudes - Sam, Emma Yoke Loo (2016)
This paper examines the factor structure and relationships between two self-report measures of career adaptability: the revised Career Maturity Inventory “Adaptability” form (rCMI-A Savickas & Porfeli, 2011) – an attitudinal measure of career adaptability, and, the Career Adapt-Abilities Scale (CAAS; Savickas & Porfeli, 2012) which conceptualizes career adaptability as a set of psychosocial resources. Confirmatory factor analyses of data collected from 750 university students in Singapore show that the two career adaptability scales are each best modeled in terms of a second-order “general” factor and several first-order factors; and, that the second-order factors correlate .43, suggesting that they measure two different but related constructs. All three (concern, curiosity and confidence) subscales of the attitudinal rCMI-A correlate most strongly with the “concern” subscale of the CAAS rather than with the corresponding sub-scale, suggesting that career adaptability as measured in the attitudinal, rCMI-A is a narrower construct than that measured in the overall CAAS. Hierarchical multiple regression analyses also show that attitudinal career adaptability does not add the prediction of boundaryless career attitudes over career adaptability resources. We conclude that the CAAS measures a broader construct of career adaptability than the rCMI A, and that it is more strongly related to “new economy”, boundaryless career attitudes, and thus a better measure for operationalizing career construction theory.